Intergenerational Disagreement and Optimal Taxation of Parental Transfers. (9th July 2016) - Pavoni, Nicola; Yazici, Hakki
Abstract: We study optimal taxation of bequests and inter vivos transfers in a model where altruistic parents and their offspring disagree on intertemporal trade-offs. We show that the laissez-faire equilibrium is Pareto inefficient, and whenever offspring are impatient from their parents' perspective, optimal policy involves a positive tax on parental transfers. Cautioned by the technical complications present in this class of models, our normative prescriptions do not rely on the assumption of differentiability of the agents' policy functions.